Radical kindness : the life-changing power of giving and receiving - Santomero, Angela C (Harper Wave, an imprint of HarperCollinsPublishers, 2019)
Angela C. Santomero, the creator, executive producer, and head writer of many of today<U+2019>s most popular educational children<U+2019>s shows believes in the radical power of kindness, on her shows, and in her life. Inspired by her mentor Fred Rogers, beloved host of the classic, award-winning PBS show Mister Rogers<U+2019> Neighborhood, Angela has dedicated her life to teaching others that when you treat yourself and others with warmth, empathy, and respect, life changing benefits follows. From the true meaning of self-care and the gift of vulnerability, to the importance of active listening or the magic of asking for help, Radical Kindness goes beyond The Golden Rule and entreaties to “be nice,” contending that kindness is the key to recognizing others, and ourselves, as worthy of love and understanding. Much like gratitude, Angela contends we need a kindness practice. A practice in which we learn to see with our hearts and act from a place of compassion. As the Dalai Lama says, “Be kind whenever possible. It is always possible.” Through practicing radical kindness<U+2014>toward ourselves, with loved ones, and to the world at large<U+2014>we can transform ourselves, our neighborhood, and our world for the better.